Intestinal Perforation in a patient with peritoneal carcinomatosis from colon cancer treated with Regorafenib. Description of a case and review of the literature - Maria Alessandra Bellia; Carmelo Sofia; Maria Adele Marino; Carmelo Mazzeo; Santino Antonio Biondo; Eugenio Cucinotta; Francesco Fleres (Radiology Case Reports, 2024)
Regorafenib is a multikinase inhibitor approved for treatment of patients with metastatic Colo-Rectal Cancer (mCRC) and Gastro-Intestinal Stromal Tumor (GIST) progression after the administration of other tyrosine-kinase inhibitors such as imatinib and sunitinib.Only a handful of severe side effects such as intestinal perforations and fistulas have been described in the literature in patients undergoing multikinase inhibitor treatment. We report a case of a patient with peritoneal mCRC who experienced an intestinal perforation during the administration of Regorafenib and review the literature. A 48-year-old man with previously resected sigmoid colon cancer and peritoneal metastatic disease under Regorafenib treatment presented to our Emergency Department with severe abdominal pain and asthenia. Abdominal X-ray and contrast-enhanced computed tomography examination revealed an intestinal perforation. The patient underwent emergency surgery which demonstrated acute diffuse peritonitis, necrosis, and perforation of a distal ileal loop affected by peritoneal metastatic disease. The necrosis of peritoneal implants on bowel walls could be regarded as a potential factor leading to intestinal perforation in metastatic colorectal cancer patients undergoing Regorafenib treatment complaining of severe abdominal pain and asthenia.Surgeons, radiologists and oncologists should always keep in mind this rare adverse event during Regorafenib administration. Appropriate diagnostic tests and treatments should be carried out.